Answer:
Algebra
Topics
How do you find the intercepts of x2y−x2+4y=0?
Algebra Graphs of Linear Equations and Functions Intercepts by Substitution
2 Answers
Gió
Mar 24, 2015
For the intercepts you set alternately x=0 and y=0 in your function:
and graphically:
Answer link
Alan P.
Mar 24, 2015
On the X-axis y=0
So
x2y−x2+4y=0
becomes
x2(0)−x2+4(0)=0
→−x2=0
→x=0
On the Y-axis x=0
and the original equation
x2y−x2+4y=0
becomes
(0)2y−(0)2+4y=0
→y=0
The only intercept for the given equation occurs at (0,0)
Answer link
Related questions
What is the x and y Intercepts?
How many intercepts can a line have?
How do you use substitution to find intercepts?
How do you identify the intercepts on a linear graph?
How do you use the x and y intercepts to graph a linear equation?
How do you find the x and y intercept for y=2x+3?
How do you find the x intercept for y=2?
What is the y intercept for the y=2 graph?
What is the y intercept for x=−1?
How do you find the x-intercept of the line
Answer:
In mathematics, the Pythagorean theorem, or Pythagoras's theorem, is a fundamental relation in Euclidean geometry among the three sides of a right triangle. It states that the area of the square whose side is the hypotenuse (the side opposite the right angle) is equal to the sum of the areas of the squares on the other two sides. This theorem can be written as an equation relating the lengths of the si…
Step-by-step explanation:
Answer:
A is your answer
Step-by-step explanation:
A
Given problem is ![\frac{(5+2i)}{(6+i)}](https://tex.z-dn.net/?f=%5Cfrac%7B%285%2B2i%29%7D%7B%286%2Bi%29%7D)
To simplify that we need to multiply and divide by conjugate of the denominator
conjugate of denominator 6+i will be 6-i as we just need to change sign of the imaginary part
Now multiply and divide by 6-i
![=\frac{(5+2i)}{(6+i)}\cdot\frac{(6-i)}{(6-i)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%285%2B2i%29%7D%7B%286%2Bi%29%7D%5Ccdot%5Cfrac%7B%286-i%29%7D%7B%286-i%29%7D)
![=\frac{30-5i+12i-2i^2}{36-6i+6i-i^2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30-5i%2B12i-2i%5E2%7D%7B36-6i%2B6i-i%5E2%7D)
![=\frac{30+7i-2i^2}{36-i^2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30%2B7i-2i%5E2%7D%7B36-i%5E2%7D)
![=\frac{30+7i-2\left(-1\right)}{36-\left(-1\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30%2B7i-2%5Cleft%28-1%5Cright%29%7D%7B36-%5Cleft%28-1%5Cright%29%7D)
![=\frac{30+7i+2}{36+1}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B30%2B7i%2B2%7D%7B36%2B1%7D)
![=\frac{32+7i}{37}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B32%2B7i%7D%7B37%7D)
![=\frac{32}{37}+\frac{7}{37}i](https://tex.z-dn.net/?f=%3D%5Cfrac%7B32%7D%7B37%7D%2B%5Cfrac%7B7%7D%7B37%7Di)
Hence final answer is ![\frac{32}{37}+\frac{7}{37}i](https://tex.z-dn.net/?f=%5Cfrac%7B32%7D%7B37%7D%2B%5Cfrac%7B7%7D%7B37%7Di)